Challenges of making a new farmer: a case study of Thailand’s Young Smart Farmer program - Kittipan Tikum; Mokbul Morshed Ahmad (Development Studies Research)
In the recent years, there has been a global decline in the number of farmers contributing to the agrarian transition. Therefore, this study delves into the case study of Thailand's ‘Young Smart Farmer (YSF)’ program, designed to counteract the declining farmer population. The study seeks to elucidate the motivations behind individuals opting to become new farmers and the challenges they face. It revealed five primary motivations to embrace farming: profitability, well-being, traditional and cultural values, taking over the family business, and social influences. This study also identifies the current challenges encountered by Thai farmers, including issues related to agricultural production, marketing, assets, seasonality and unexpected shocks, and criticism. To improve the program’s effectiveness, this study recommends four key strategies: establishing knowledge certification linkages, refinement of workshops and training content, expanding farmer networks, and implementing policies aimed at nurturing new farming talent.